Application of technology to empower women in social entrepreneurship: A review - Saikat Gochhait; Renuka Lenka; Salamzadeh Aidin (Entrepreneurial Business and Economics Review (EBER), 2025)
Objective: As digital innovation and adoption grow, women entrepreneurs have more chances than ever to launch their companies and support them in realizing their full potential. Technology makes it easier for women to access resources and their market and thus enables them to expand inclusively in the business sector. This research, which is based on the transformational learning theory, shows how technology adoption helps women entrepreneurs develop and run their companies more successfully than they have in the past. Research Design & Methods: To provide an overview of the influence of digital technology adoption and the expansion of women's social entrepreneurship on the socio-economic stability of business operations, this study offers a comprehensive assessment of the literature with the help of qualitative study, encompassing 159 research papers published between 1993 and 2023. The purpose of the study is to explain how digital adoption affects female entrepreneurs. Using PRISMA, we implemented a comprehensive key search technique in the SCOPUS database. Findings: Technology significantly boosts women's participation in social entrepreneurship, as it allows them easier access to digital resources, funding platforms, or networks than men. It also helps in developing skills and fosters cooperation. Moreover, it easily removes long-standing obstacles. These transformations allow women not only to be more innovative and to scale their ventures up in size but also to have an area-wide social and economic benefit. Implications & Recommendations: Technology can bridge gender gaps in entrepreneurship. It gives women greater access to resources, training and networks. Suggestions include creating digital literacy programs, increasing the flow of capital through technological platforms and nurturing online communities that welcome women social entrepreneurs. This is not just a matter of promoting women-led businesses. It applies equally to the practice of sustainable development. Contribution & Value Added: In social entrepreneurship, technology makes it easier for women to access resources, networks, and education. Theories like empowerment, social capital, and human capital illustrate how new media drives empowerment, and promotes cooperation among women and improved skills. Businesses grow faster as a result of diffusion of innovation, a process that means more women can engage in production and consumption activities which change the nature of economic society.
Keywords: J16; L26; J24; O30; B54; 330; digitalization; women; social entrepreneurship; technology transformation